SRG/ART-XC, Swift, NICER, and NuSTAR study of different states of the transient X-ray pulsar MAXI J0903-531 - Tsygankov Sergey S; Molkov Sergey V; Doroshenko Victor; Mushtukov Alexander A; Mereminskiy Ilya A; Semena Andrei N; Thalhammer Philipp; Wilms Jörn; Lutovinov Alexander A (EDP Sciences, 2023)
The results of the broadband spectral and timing study of the recently discovered transient X-ray pulsar MAXI J0903-531 in a wide range of luminosities that differ by a factor of ~30 are reported. The observed X-ray spectrum in both states can be described as a classical pulsar-like spectrum consisting of a power law with a high-energy cutoff. We argue that the absence of the spectrum transformation to the two-hump structure that is expected at low fluxes indicates that the magnetic field of the neutron star is relatively weak below (2-3) x 1012 G. This estimate is consistent with other indirect constraints and non-detection of any absorption features that might be interpreted as a cyclotron absorption line. The timing analysis of the NuSTAR data revealed only slight variations of a single-peaked pulse profile of the source as a function of the energy band and mass accretion rate. In both intensity states, the pulsed fraction increases from 40% to roughly 80% with the energy. Finally, we were also able to obtain the orbital solution for the binary system using data from the Fermi/GBM, NICER, and NuSTAR instruments.